2013
DOI: 10.1371/journal.pone.0062410
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Adrenergic Ventrolateral Medullary Cells Are Activated whereas Precerebellar Lateral Reticular Nucleus Neurons Are Suppressed during REM Sleep

Abstract: Rapid eye movement sleep (REMS) is generated in the brainstem by a distributed network of neurochemically distinct neurons. In the pons, the main subtypes are cholinergic and glutamatergic REMS-on cells and aminergic REMS-off cells. Pontine REMS-on cells send axons to the ventrolateral medulla (VLM), but little is known about REMS-related activity of VLM cells. In urethane-anesthetized rats, dorsomedial pontine injections of carbachol trigger REMS-like episodes that include cortical and hippocampal activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 123 publications
(199 reference statements)
2
12
0
1
Order By: Relevance
“…However, data show that adrenergic C1 neurons have spontaneous activity in urethane-anesthetized rats (Huangfu et al, 1992; Verberne et al, 1999). Our recent electrophysiological data confirm that C1 neurons are spontaneously active and show that they are activated during the REM sleep-like episodes (Stettner et al, 2013). It is possible that the lack of significant correlation between c-Fos expression and the amount of prior time spent in REM sleep-like episodes for the combined group of A1 and C1 neurons was caused by opposite behaviors of A1 and C1 neurons and our limited ability to distinguish between A1 and C1 neurons based solely on anatomical landmarks and tyrosine hydroxylase immunohistochemistry (Rukhadze et al, 2008).…”
Section: The Sources Of Na Excitatory Input To XII Motoneurons and supporting
confidence: 66%
“…However, data show that adrenergic C1 neurons have spontaneous activity in urethane-anesthetized rats (Huangfu et al, 1992; Verberne et al, 1999). Our recent electrophysiological data confirm that C1 neurons are spontaneously active and show that they are activated during the REM sleep-like episodes (Stettner et al, 2013). It is possible that the lack of significant correlation between c-Fos expression and the amount of prior time spent in REM sleep-like episodes for the combined group of A1 and C1 neurons was caused by opposite behaviors of A1 and C1 neurons and our limited ability to distinguish between A1 and C1 neurons based solely on anatomical landmarks and tyrosine hydroxylase immunohistochemistry (Rukhadze et al, 2008).…”
Section: The Sources Of Na Excitatory Input To XII Motoneurons and supporting
confidence: 66%
“…This is supported by our finding that focal injection of yohimbine at bilateral A7 and A5 neurons produced similar beneficial effects on HM activity and obstructive apnea-induced hLTF, as did systemic yohimbine (Figure 6), suggesting that postsynaptic α 2 -adrenoceptors on the dendrites and/or cell bodies of these pontine noradrenergic neurons (rather than α 2 -autoceptors on their distal axonal terminals presynaptic to the HMs) were likely the sites of action of yohimbine therapy. Indeed, certain medullary adrenergic neurons (such as the C1 cell group) are known to be active during REM sleep and exert inhibitory influences on pontine noradrenergic neurons via α 2 -adrenoceptors (44,45), although recent studies revealed that a subset of C1 neurons may paradoxically also exert stimulation frequency-dependent excitatory influences on pontine noradrenergic neurons (46). Of note, previous studies have shown that HMs may be subject to an α 2C -adrenoceptor (but not α 2A -adrenoceptor) subtype-mediated inhibition (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Fos expression in A2/C2, A5, SubC and A7 neurons strongly correlates with parameters of pharmacologically induced REM sleep-like states, which suggests a state-dependent nature of their activity, whereas A1/C1 neurons did not show a significant correlation (Rukhadze et al, 2008). The fact that A1/C1 neurons did not significantly decrease their activity during REM sleep-like states could be explained by activation of C1 neurons during REM sleep-like state (Stettner et al, 2013). Clearly, further studies are needed to dissociate the mixed population of A1/C1 neurons and establish the functional relationship between GG muscle activity and noradrenergic A1 and adrenergic C1 neurons during sleep-wake states in behaving mice.…”
Section: Discussionmentioning
confidence: 99%